2000
DOI: 10.1021/bi992416z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Analysis of Apoxin I, a Snake Venom-Derived Apoptosis-Inducing Factor withl-Amino Acid Oxidase Activity

Abstract: We previously purified apoxin I, an apoptosis-inducing factor with L-amino acid oxidase (LAO) activity, from Western diamondback rattlesnake venom. To determine the primary structure of apoxin I, we cloned its cDNA. The amino acid sequence showed that apoxin I has an FAD binding domain and shares homology with L-amino acid oxidase (LAO) from Neurospora crassa, human monoamine oxidase B, and mouse interleukin 4-induced F1G1 protein. The full-length apoxin I has an N-terminal signal sequence that is processed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 19 publications
(26 reference statements)
5
60
1
4
Order By: Relevance
“…3,4 While sharing high similarity over the majority of the sequence (547 amino acids of the 567 in the human sequence), the human and mouse proteins diverge substantially at their C-terminal region. 4 The IL4I1 protein shares the highest similarity with proteins presenting L-amino acid oxidase (LAAO) activity, such as snake venom LAAO, 7,8 and mouse milk LAAO. 9 Recently, Mason et al have demonstrated that mouse IL4I1 (mIL4I1) possesses an LAAO activity toward aromatic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 While sharing high similarity over the majority of the sequence (547 amino acids of the 567 in the human sequence), the human and mouse proteins diverge substantially at their C-terminal region. 4 The IL4I1 protein shares the highest similarity with proteins presenting L-amino acid oxidase (LAAO) activity, such as snake venom LAAO, 7,8 and mouse milk LAAO. 9 Recently, Mason et al have demonstrated that mouse IL4I1 (mIL4I1) possesses an LAAO activity toward aromatic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies on LAAO from Crotalus atrox, expressed in eukaryotic cells, revealed that inhibition of N-glycosylation blocks its secretion to the medium and abolishes activity of the residually secreted enzyme. 8 The glycan moiety of LAAO has been implicated in docking the enzyme to the surface of the host cell and enhancing the localization of high concentrations of H 2 O 2 . In fact, the finding that LAAO-induced apoptosis is distinct from that caused by exogenous hydrogen peroxide supports the idea that the mode of hydrogen peroxide delivery is an important factor in inducing apoptotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced FAD co-factor is regenerated by reaction with dioxygen, leading to the formation of hydrogen peroxide, a known ROS with apoptotic potential, as mentioned previously. In fact, LAAO has been shown to induce cell death in several mammalian cell lines, such as vascular endothelial cells (Araki et al, 1993), mouse lymphocytic leukaemia cells, human T cells (Suhr and Kim, 1996;Torii et al, 2000), human promyelocytic leukaemia cells and human embryonic kidney cells (Torii et al, 1997(Torii et al, , 2000. In addition, LAAO exhibits antibacterial and antiviral properties, inhibiting the growth of both Gram-positive and -negative prokaryotes as well as HIV (Skarnes, 1970;Zhang et al, 2003Zhang et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%